An Outbreak of Hepatic Veno-Occlusive Disease in Western Afghanistan Associated with Exposure to Wheat Flour Contaminated with Pyrrolizidine Alkaloids - Faizullah Kakar; Zarif Akbarian; Toby Leslie; Mir Lais Mustafa; John Watson; Hans P. van Egmond; Mohammad Fahim Omar; Jawad Mofleh (Journal of Toxicology)
Pyrrolizidine alakloids (PAs) are known to cause hepatic veno-occlusive disease (VOD). Outbreaks have occurred in Western Afghanistan since 1974, the latest in February 2008. We conducted an outbreak investigation using a case-control design. Sixty-seven cases of VOD were compared with 199 community controls. Consumption of bread was strongly associated with disease (adjusted odds ratio: 35.8 [95%CI: 7.6–168.2]). Toxic doses of PA were found in plant extracts and in samples of wheat flour taken from the study area. Compared to wheat flour there was 1000 times less PA in milk and whey and in water samples the PA content was zero. Although direct analysis was not possible, contaminated wheat flour used to make bread was the likely source of PA causing the outbreak. Eating a more varied diet including meat and fruit may be protective. Prevention and control measures will rely on community awareness and agricultural interventions to ensure safety of the food supply.